2020
DOI: 10.3390/ijms21041182
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Salivary Gland AQP5 under Normal and Pathologic Conditions

Abstract: Aquaporin 5 (AQP5) plays an important role in the salivary gland function. The mRNA and protein for AQP5 are expressed in the acini from embryonic days E13-16 and E17-18, respectively and for entire postnatal days. Ligation-reopening of main excretory duct induces changes in the AQP5 level which would give an insight for mechanism of regeneration/self-duplication of acinar cells. The AQP5 level in the submandibular gland (SMG) decreases by chorda tympani denervation (CTD) via activation autophagosome, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 78 publications
(94 reference statements)
1
45
0
1
Order By: Relevance
“…Immunohistological studies revealed that AQP4 expression was located at the basal region of acinar cells, at the apicolateral membrane of intercalated and striated ducts, and in myoepithelial cells [ 21 ]. AQP5 protein is predominantly expressed at the apical membrane, with slight expression at the basolateral membrane of serous and mucous acini [ 12 , 19 , 22 ]. In contrast to intercalated ductal cells expressing AQP5 during SG development, mature ducts are devoid of AQP5 labeling [ 18 ].…”
Section: Cellular Distribution Of Aqps In Adult Sg Subsectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistological studies revealed that AQP4 expression was located at the basal region of acinar cells, at the apicolateral membrane of intercalated and striated ducts, and in myoepithelial cells [ 21 ]. AQP5 protein is predominantly expressed at the apical membrane, with slight expression at the basolateral membrane of serous and mucous acini [ 12 , 19 , 22 ]. In contrast to intercalated ductal cells expressing AQP5 during SG development, mature ducts are devoid of AQP5 labeling [ 18 ].…”
Section: Cellular Distribution Of Aqps In Adult Sg Subsectionmentioning
confidence: 99%
“…AQP8 is also expressed by myoepithelial cells [ 24 ]. Both the apical and basolateral membranes of acinar cells display positive AQP5 labeling [ 17 , 22 , 25 , 26 ]. In addition, intercalated ducts express AQP5 at their apical membrane [ 27 ].…”
Section: Cellular Distribution Of Aqps In Adult Sg Subsectionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 30, 2020. ; https://doi.org/10.1101/2020.05. 26 human c-Kit ligand also known as human stem cell factor (hSCF), which makes them ideal to study the regenerative properties of c-KIT-expressing putative human salivary stem cells (10).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 30, 2020. ; https://doi.org/10.1101/2020.05. 26 was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Resultsmentioning
confidence: 99%
“…Innervation distribution and modification of neuropeptides associated with the autonomic nervous system have been observed in the developing rat palatine glands (48). The autonomic nervous system affects the properties of the salivary secretions as sympathetic stimulation generally results in a small volume of saliva with high viscosity, while parasympathetic stimulation results in a large volume with low viscosity (49). It has been reported that parasympathectomy downregulated AQP5 protein levels in rat submandibular glands, but sympathectomy caused little change in the protein levels of AQP5, suggesting that AQP5 is regulated by the parasympathetic nervous system (50).…”
Section: Discussionmentioning
confidence: 99%